1997
DOI: 10.1016/s0960-9822(06)00057-1
|View full text |Cite
|
Sign up to set email alerts
|

CD22 is a negative regulator of B-cell receptor signalling

Abstract: . The absence of CD22 expression lowers the signalling threshold for BCR-crosslinking and can thus influence the fate of the B cell. We propose that the low threshold leads to hyperresponsiveness of the B cells and a chronic basal activation. In this model, engagement of the receptor without T-cell help leads to an increased induction of apoptosis, thus explaining the shorter lifespan of CD22(-/-) B cells and the low response to T-cell independent antigens. The alteration in B-cell phenotype and the higher lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
392
2
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 403 publications
(429 citation statements)
references
References 41 publications
31
392
2
3
Order By: Relevance
“…38,39 Finally, we demonstrated that E2 downregulates expression of CD22 (encoded by Cd22), an inhibitory receptor on B cells that attenuates Ca 2 þ levels induced after B-cell receptor signaling. 40 Considerable evidence supports the hypothesis that depressed levels of CD22 on B cells can promote IgG ANA production. [41][42][43] In contrast to our results, Grimaldi et al 44 found that mRNA and surface protein expression of Cd22 were upregulated in response to E2 in BALB/c mice and proposed that this upregulation may be involved in the escape of autoreactive B cells from tolerance.…”
Section: Discussionmentioning
confidence: 94%
“…38,39 Finally, we demonstrated that E2 downregulates expression of CD22 (encoded by Cd22), an inhibitory receptor on B cells that attenuates Ca 2 þ levels induced after B-cell receptor signaling. 40 Considerable evidence supports the hypothesis that depressed levels of CD22 on B cells can promote IgG ANA production. [41][42][43] In contrast to our results, Grimaldi et al 44 found that mRNA and surface protein expression of Cd22 were upregulated in response to E2 in BALB/c mice and proposed that this upregulation may be involved in the escape of autoreactive B cells from tolerance.…”
Section: Discussionmentioning
confidence: 94%
“…Immobilized epratuzumab when crosslinked with anti-IgG can induce several effects in assays performed in vitro based on the specific cell type studied. For CD22-positive B-cell lymphoma, immobilized but not soluble epratuzumab can inhibit cellular proliferation, regardless of crosslinking (Nitschke et al, 1997). CD22 has been observed to negatively regulate signaling (PawlakByczkowska et al, 1989;O'Keefe et al, 1996;Otipoby et al, 1996;Sato et al, 1996), although other studies with human B-lymphoma cells suggest an involvement of CD22 with the BCR that can inhibit proliferation (Nitschke et al, 1997).…”
Section: Cd22 As a Target For Immunotherapy In B-cell Malignanciesmentioning
confidence: 99%
“…A humanized IgG 1(k) version of LL2 (called hLL2 or epratuzumab) was generated for potential clinical application (Leonard et al, 2003). Mechanisms of action appear to differ from those of rituximab, specifically by the ability of epratuzumab to induce CD22 phosphorylation (Leung et al, 1995), modulate the BCR, as well as to mediate a moderate degree of ADCC, without induction of apoptosis or complement-mediated cell lysis (Leung et al, 1995;Nitschke et al, 1997). Epratuzumab has also demonstrated clinical activity in NHL, systemic lupus erythematosis (SLE) and Sjo¨gren's syndrome, while providing only moderate B-cell depletion (in contrast to rituximab) (Griffiths et al, 2003;Leonard et al, 2005a, b;Do¨rner et al, 2006;.…”
Section: Cd22 As a Target For Immunotherapy In B-cell Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease may be the result of a trafficking defect of B cells back to the bone marrow from the periphery. One molecule that has been shown to be essential for trafficking of B cells from the periphery specifically to the bone marrow is the signaling molecule CD22 [12]. Therefore, we analyzed Ik7tg B cells by flow cytometry to determine if they have altered levels of CD22 on their surface.…”
Section: Decreased Numbers Of Recirculating B Cells In Vk2-ik7tg Micementioning
confidence: 99%